Stereotyp kobiety powstały we współczesnym rosyjskim i polskim społeczeństwie (na podstawie eksperymentu asocjacyjnego) - Oshchepkova, Anastasia (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present article refers to a free associative experiment and its results. The author tries to determine what values are represented with the term “woman” in Russian and Polish societies. The article is focused on similarities as well as differences between the Polish and Russian respondents. In order to achieve this, the author classified and divided the lexis proposed by the respondents into groups. Those groups were thoroughly discussed and analyzed. By doing this, the author tries to look into the subconsciousness of a young modern person. Thus, in the article the answers to the following questions can be found: do stereotypes concerning women still exist?; what do Poles and Russians think about that?; is their way of thinking convergent or not? The experiment described in the article was conducted during 2011–2013 among 100 Poles and 200 Russians under the age of 30. It was carried out by means of series of surveys; in these surveys respondents were asked to provide words and expressions they associate with the term “woman”. Classified lexical units were then analyzed, the conclusion was drawn on the basis of this analysis. The text is divided into parts. Every part revolves around classification of responses of both groups: first group — Russians (both men and women), second — Poles (men and women). The assignment comprises four diagrams that picture the percentage of responses in the groups.